Weight Gains from Trade in Foods: Evidence from Mexico - Osea Giuntella; Matthias Rieger; Lorenzo Rotunno (Institute of Labor Economics (IZA), 2019)
In this paper, we investigate the effects of trade in foods on obesity in Mexico. To do so, we match data on Mexican food imports from the U.S. with anthropometric and food expenditure data. Our findings suggest that exposure to food imports from the U.S. can explain up to twenty percent of the rise in obesity prevalence among Mexican women between 1988 and 2012. Pro-obesity effects are driven by areas more exposed to unhealthy food imports. We also find evidence in favour of a price mechanism. By linking trade flows to obesity, the paper sheds light on an important channel through which globalisation may affect health.
Keywords: F60; F61; I10; I12; 330; trade; obesity; nutrition transition; Mexico